An explorative study of school performance and antipsychotic medication. Issue 1 (December 2016) - van der Schans, J.; Vardar, S.; Çiçek, R.; Bos, H.; Hoekstra, P.; de Vries, T.; Hak, E.
Abstract Background Antipsychotic therapy can reduce severe symptoms of psychiatric disorders, however, data on school performance among children on such treatment are lacking. The objective was to explore school performance among children using antipsychotic drugs at the end of primary education. Methods A cross-sectional study was conducted using the University Groningen pharmacy database linked to academic achievement scores at the end of primary school (Dutch Cito-test) obtained from Statistics Netherlands. Mean Cito-test scores and standard deviations were obtained for children on antipsychotic therapy and reference children, and statistically compared using analyses of covariance. In addition, differences in subgroups as boys versus girls, ethnicity, household income, and late starters (start date within 12 months of the Cito-test) versus early starters (start date > 12 months before the Cito-test) were tested. Results In all, data from 7994 children could be linked to Cito-test scores. At the time of the Cito-test, 45 (0.6 %) were on treatment with antipsychotics. Children using antipsychotics scored on average 3.6 points lower than the reference peer group (534.5 ± 9.5). Scores were different across gender and levels of household income (p < 0.05 ). Scores of early starters were significantly higher than starters within 12 months (533.7 ± 1.7 vs. 524.1 ± 2.6). Conclusion This first exploration showed that children on antipsychotic treatment have lower school performance compared to the reference peer group at the end of primary school. This was most noticeable for girls, but early starters were less affected than later starters. Due to the observational cross-sectional nature of this study, no causality can be inferred, but the results indicate that school performance should be closely monitored and causes of underperformance despite treatment warrants more research.